Intrauterine balloon failure: unrecognized placenta accreta spectrum disorders - K. Tamura; H. Takahashi; S. Uchida; M. Ogoyama; R. Usui; S. Matsubara (Clinical and Experimental Obstetrics & Gynecology)
Several studies indicate that intrauterine balloon (IUB) use is less effective for postpartum hemorrhage (PPH) due to placenta accreta spectrum (PAS) disorders than that due to atonic bleeding. IUB failed to achieve hemostasis because the present two cases had normally positioned PAS. Case Report: A 37-year-old woman was transferred due to PPH. She vaginally delivered. The placenta was without macroscopic defect. Atonic bleeding was suspected. An IUB was placed, without achieving hemostasis. Her status deteriorated, necessitating a hysterectomy. The placenta remained, adhering to the uterine body. Histological examination revealed placenta accreta. The second case was a 40-year-old woman that was transferred due to PPH of atonic bleeding after vaginal delivery. The placenta was without macroscopic defect. An IUB was placed, without hemostasis, and was subsequently was removed. Conservative treatment achieved hemostasis. An Ultrasound revealed the placenta in the uterine body. We diagnosed her with clinical PAS. Nonprevia PAS may be present when an IUB fails to achieve hemostasis.